EFFECT OF A PARKED VEHICLE ON INDIVIDUAL VEHICULAR SPEEDS ON TWO-LANE TWO-WAY INTERURBAN HIGHWAYS - SURYO PUTRANTO, LEKSMONO
EFFECT OF A PARKED VEHICLE ON INDIVIDUAL VEHICULAR SPEEDS ON TWO-LANE TWO-WAY INTERURBAN HIGHWAYS, Putranto, Leksmono Suryo, 1995, Program Magister Sistem dan Teknik Jalan Raya, Program Pascasarjana, Institut Teknologi Bandung The objectives of this thesis were (1) to evaluate and quantify the effect of a vehicle parked on the shoulder and /or carriageway on individual vehicular speeds, (2) to compare the results with macroscopic data from the Indonesian Highway Capacity Manual Project and (3) to recommend a method for determination of the level of influence of a parked vehicle in analysis of level of\' performance. The study was conducted on a two-lane two-way undivided interurban highway that was located in flat terrain with relatively straight sections and two-way traffic flow between 600 and 1600 l vu per hour. Three levels of blockage were studied, i.e. shoulder blockage, 0.5 m carriageway blockage and 1 m carriageway blockage. The blockage was a deliberately parked vehicle. Measurement of speeds in both directions was conducted 150 m before, at, and 80 m beyond the blockage For all levels of blockage significant speed reduction was found for the opposed condition Cup to 11 kph). The speed reductions due to shoulder blockage and 0.5 m carriageway blockage were similar, while a 1 m carriageway blockage caused greater speed reduction. For an effective average shoulder width between 1 and 2 m, speed reduction observed in this study was almost similar to values given in the Indonesian Highway Capacity Manual for Interurban Roads, while for wider and narrower shoulders the values were similar for low and very low side friction classes only. The level of\' influence of a parked vehicle on the level of performance of two-lane two-way highways can be determined from its speed reduction effect. Since considerable speed reduction due to a parked vehicle was statistically proved, it is recommended that stopping / parking regulations be rigorously enforced.